Equity and Fiscal Policy : The Income Distribution Effects of Taxation and Social Spending in Central America - Cubero, Rodrigo (IMF Working Papers; Working Paper, 2010)
How does fiscal policy fare in improving the underlying income distribution in Central America? We integrate the data from a number of existing tax and public expenditure studies for the countries in the region and find that the distributional effect of taxation is regressive but small. In contrast, the redistributive impact of social spending is large and progressive, leading to a progressive net redistributive effect in all countries of the region. We also show that raising tax revenues and devoting the proceeds to social spending would unambiguously improve the income of the poorest households.